Understanding the Connection between Urbanization and Hydrometeorological Disasters: an Experience from Central Java Province, Indonesia. Issue 1 (1st September 2022) - Dewi, R S; Handayani, W; Rudiarto, I; Artiningsih,
Abstract: Climate change is one of the development challenges, both at the global, national, and regional levels. In recent years, the impact of climate change is increasingly affect the world community. Various studies state that the factor that exacerbates climate change comes from massive human activities, causing the production of the increasing of greenhouse gases. The growth in population and rapid urbanization causes urban expansion. Land conversion is unavoidable, escalates pressure on the environment, causing hydrometeorological disasters such as floods to occur more frequently. Some of them even claimed many lives and caused material losses. This study aims to investigate the connection between urbanization and hydrometeorological disasters in Central Java Province, as an effort to understand the characteristics of the region in supporting adaptation to climate change. The method used is overlay analysis through GIS by using data on the rural urban status, building density, and disaster events in Central Java Province in 2020. Based on the results of the analysis, it is known that the existence of massive urbanization correlates to the occurrence of disasters, depicted by several spots in Central Java Province.